SPS120 : Creative movement and exercise / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
Focuses on the practical application of handling group exercise session with effective movements that generating from proper music and steps choreography that can enhance people engaging with exercise.